2007
DOI: 10.1111/j.1467-8624.2007.01043.x
|View full text |Cite
|
Sign up to set email alerts
|

Change in Atypical Maternal Behavior Predicts Change in Attachment Disorganization From 12 to 24 Months in a High‐Risk Sample

Abstract: This longitudinal study examined links between disorganization and atypical maternal behavior at 12 and 24 months in 71 adolescent mother-child dyads. Organized attachment and maternal not disrupted behavior were more stable than disorganization and disrupted behavior, respectively. At both ages, disorganization and maternal disrupted behavior were significantly correlated. Change in atypical maternal behavior predicted change in disorganization across time. The results provide substantial support for extant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 68 publications
7
21
0
Order By: Relevance
“…Its findings are consistent with previous studies of the behavioural expressions of disorganized attachment [14] and provide a valuable initial portrait of the development of representational strategies for dealing with attachment-related information. Although the impact of premature birth on maternal interactive behaviour [4] and on child attachment [5] has been documented in previous reports, associations between maternal sensitivity and child attachment had never been examined in preterm samples.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Its findings are consistent with previous studies of the behavioural expressions of disorganized attachment [14] and provide a valuable initial portrait of the development of representational strategies for dealing with attachment-related information. Although the impact of premature birth on maternal interactive behaviour [4] and on child attachment [5] has been documented in previous reports, associations between maternal sensitivity and child attachment had never been examined in preterm samples.…”
Section: Discussionsupporting
confidence: 88%
“…Because the association between maternal interactive behaviour and attachment has been shown to vary as a function of the measures of sensitivity [3], some researchers have suggested that assessing maternal sensitivity as a single global dimension may fail to capture important variation in the quality of interactions that influence attachment [14]. In this study, therefore, more detailed descriptions of maternal interactions (i.e.…”
Section: Introductionmentioning
confidence: 98%
“…The AMBIANCE measure has expanded its use to caregivers of four-month-old infants (e.g., Benoit, Waley, & Goldberg, 2001;Kelly, 2004;Kelly et al, 2003) and 24-month-old toddlers (e.g., Forbes et al, 2007). Kelly et al (2003) examined the stability of atypical caregiver behaviors over 10 months in a sample of 51 middle-to-upper-class mother-infant dyads.…”
mentioning
confidence: 98%
“…The Atypical Maternal Behavior Instrument for Assessment and Classification (AMBIANCE; Bronfman, Madigan, & Lyons-Ruth, 2008) involves recording the number of atypical behaviors displayed by a caregiver in each dimension during interactions with the infant, assigning an overall level of atypical communication, and classifying the caregiver behavior as ''disrupted'' or ''not disrupted'' in communication with the infant. The AMBIANCE has been used to code atypical caregiver behaviors in a variety of populations and across several contexts, including the Strange Situation (Gervai et al, 2007;Goldberg, Benoit, Blokland, & Madigan, 2003;Grienenberger, Kelly, & Slade, 2005;Madigan, Benoit, & Boucher, in press), unstructured play , reunion episodes outside of the Strange Situation (Forbes, Evans, Moran, & Pederson, 2007), and during faceto-face interactions (Kelly, Ueng-McHale, Grienenberger, & Slade, 2003). Regardless of the context in which atypical caregiver behaviors have been observed, several independent studies implicate some form of markedly anomalous caregiver interactive behaviors in the development of disorganized attachment relationships.…”
mentioning
confidence: 98%
“…One of the main tenets of attachment theory is that the mother repeats her own maternal attachment representations which in turn affect the infant's attachment process, with the possibility of compounding dysfunction throughout the generations (Forbes et al 2007). These internal representations are self-perpetuating because they create responses consistent with their relational experiences (Thompson 1999).…”
Section: Attachmentmentioning
confidence: 99%